A conceptual framework to mitigate the adverse effects of surface urban heat islands through urban acupuncture: a two-phase scenario of diagnosis and prescription at the neighborhood scale - Moussavi A., S. Mohammad Reza; Lak, Azadeh; Tabrizi, Nasibeh (Frontiers in Environmental Science, 2024)
Rising temperatures, a major global environmental challenge, negatively impact health, the environment, society, and the economy. Surface Urban Heat Islands (SUHI), exacerbated by urbanization and climate change, intensify vulnerabilities for urban areas and residents. Urban planning and design aime to reduce these vulnerabilities through large-scale and small-scale interventions. However, addressing the significance of the capillary effects resulting from small-scale interventions and bottom-up community engagement is important. Urban acupuncture (UA) is an emerging approach in contemporary urban planning and design that focuses on small-scale interventions to mitigate the effects of SUHIs at the community level. This study develops a framework for mitigating the impacts of SUHIs through UA implementation in urban design. The proposed framework consists of two key phases: diagnosis and prescription. During the diagnosis phase, we analyzed heat-vulnerable points to identify indicators contributing to the development and exacerbation of the SUHIs. Then, we employed the Matrix of Cross Impact Multiplications Applied to a Classification (MICMAC) technique to comprehensively assess 75 influential indicators related to urban structure across various aspects and scales, focusing on the mesoscale. Among them, 30 leading indicators were identified, of which environmental and morphological indicators emerged as significant catalysts. Moving on to the prescription phase, we developed a UA-based framework called the “5 Wh Question” which addresses five fundamental questions: why, who, what, how, and where. Our findings can provide comprehensive solutions for policymakers and urban planners to address the identified heat-vulnerable points.